Bank Financial Performance in Indonesia: Customer Assisted and Customer Transparent - Ossi Ferli; Ilham Wahyu Alfajri (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2020)
The purpose of this research is to determine the effect of innovation technology on the financial performance. Population of this research are 30 banks in Indonesia Stock Exchange in 2017 that conduct online banking. Samples for each bank are average from 3 respondents. The independent variable uses primary data obtained from questionnaire are Customer Independent, Customer Assisted, and Customer Transparent as a calculation of Innovation technology. The dependent variables use secondary data from financial reports in Indonesia Stock Exchange are financial performance which uses 5 indicators consisting of Non Performing Loans (NPL), Return on Assets (ROA) and Capital Adequacy Ratio (CAR). The data processing method used is the Partial Least Square (PLS) method using Smart PLS 3.0 software. The results show that Customer Independent have no significant effect on financial performance. Customer Assisted and Customer Transparent have a positive significant on financial performance